Effects of Temperature Variation on the Fatty Acid Composition of Candida utilis - McMurrough, I. (1971)
The fatty acid compositions of various cultures of the yeast Candida utilis NCYC 321 were analyzed by gas-liquid chromatography of the methyl esters obtained from the lipids in chloroform-methanol extracts of the cells. Over a wide range of growth conditions C. utilis contained mainly 16:0, 16:1, 18:1, 18:2, and 18:3 fatty acids in variable proportions. The most variable aspect of the fatty-acid composition of C. utilis was in the relative proportions of 18:1, 18:2, and 18:3 acids. During batch growth at 30 C, the relative proportions of 18:3 decreased, whereas 18:1 increased as the cultures aged. Batch cultures grown at low temperatures maintained higher proportions of 18:3 acids than cultures grown at 30 C. When stationary cultures were replenished with fresh medium under aerobic conditions, there was an abrupt increase in the proportion of 18:3 with a concomitant decrease in 18:1 acids in the cells. The fatty acid composition of cells grown in a chemostat at 30 C did not vary much in response to changes in either the growth rate or the growth-limiting substrate. Chemostat-grown cells contained highest proportions of 18:3 acid when grown under conditions of glucose-limitation at low temperatures.